Comparative Efficacy of Bispectral Index Monitoring and Clinical Assessment in The Recovery of Patients Undergoing Open Renal Surgery: A Randomized, Double-Blind Study - Khoshrang, Hossein; Nemati, Maryam; Mokhtari, Gholamreza; Pourreza, Farshid; Atrkar Roshan, Zahra; Dehghan Najmabadi, Afsane; Esmaeili, Samaneh; Rastjou Herfeh, Nadia (Annals of Anesthesiology and Critical Care, 2016)
Background and Aims: Maintaining the sufficient depth of anesthesia with an adequate anesthetic drug dosage in patients undergoing surgery is one of the most significant issues. Inadequate depth of anesthesia can cause significant disturbances in hemodynamic parameters. In this study, clinical assessment and bispectral (BIS) index monitoring compare the depth of general anesthesia and recovery time in patients undergoing open renal surgery. Method: In this double-blind, randomized, controlled trial, all patients undergoingopenrenal surgery were enrolledandrandomly divided into a BIS group and clinical assessment group (control). In the BIS group, the electrodes of BIS monitoring system were placed on frontal and temporal lobes of the patient. The time of eye opening, verbal response to verbal stimulation, extubation time, the duration of stay in the recovery unit, the first-time of narcotic usage, and total dosage of intravenous narcotics were assessed in 2 groups. Results: A total of 96 patients were enrolled. Sex, age, BMI, duration of surgery, length of stay in the recovery room and first-time narcotic drug usage were not significantly different in the two groups. However, the length of time from the anesthetic drug discontinuation to eye opening, verbal responses to verbal stimulation and extubation was significantly lower in the BIS group than the control group, respectively (P = 0.002, P = 0.007, P = 0.019). Conclusions: The evaluation of the aneasthesia status of patients based on the BIS index would be more efficient in decreasing the emergence anaesthesia including eye opening, verbal response, extubation after anesthesia